Tiktok trends in higher education as a tool to improve english fluency in speaking skills (2022)
This exploratory action research study, implemented the use of the Tik Tok trends as a tool in the teaching and learning process to improve the lack of fluency in speaking skills of students in an English IV course, of an educational institution of higher education in the public sector in the Caribbean coast of Colombia, more specifically in the city of Cartagena, Bolívar. The population sample were 17 students, 14 women and 3 men between the ages of 19 and 24, belonging to the English IV course of a professional program in foreign languages during the academic period of 2022-2. In addition, this study explored if this new tool can be an influential factor in the students' motivation. The results of this exploratory research show that time is a fundamental variable in accordance to fluency in speaking skills. In addition, it was possible to prove that motivation is influenced by the insertion of this new tool.